Vers une optimisation de la compétence lectorale défectueuse. Cas de la recherche-action comme scénario pédagogique de remédiation - Loudiyi, Mourad (Ponti/Ponts, 2021)
The objective of the present study is to report on the impact of the end-of-study project on the problematization and conceptualization of the reading difficulties among Moroccan learners. We would like to see the extent to which action research can yield an optimal transferability of the pedagogical scenario. Following a problem situation where learners develop awareness of the reading challenges they face, the didactic aim implemented through the remediation scenario allows for the re-contextualization of reading skills development. We start by presenting the adopted approach and its theoretical foundations. After that, we demonstrate that through our support and supervision of novice teachers, the pedagogical scenario of remediation can be considered as a practice of direct correction and readjustment of deficiencies. This is identified through a diagnostic assessment, aiming primarily at building and developing the reading competence as defined by the official guidelines and syllabi in Morocco. Through the present study, we intend to support the idea that action research is a major tool of integrating remediation and establishing a pedagogical-didactic approach which takes into account the diversity of students’ needs and difficulties.